Important Finding for COVID-19 Pandemic: Hydrocephalus-producing effect of Vaporized Alcohol Disinfectant - Kanat, Ayhan; Aydin, Mehmet Dumlu; Sahin, Balkan; Daltaban, Iskender Samet; Gel, Mehmet Selim; Guvercin, Ali Riza; Demirtas, Rabia (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Alcohol exposure may cause hydrocephalus, but the effect of vaporized nasal alcohol exposure on the choroid plexus, and ependymal cells, and the relationship between alcohol exposure and developing hydrocephalus are not well known. This subject was investigated.Methods Twenty-four male (∼380 g) Wistar rats were used in this study. The animals were divided into three groups, as the control, sham and study groups. The study group was further divided into two groups as the group exposed to low or high dose of alcohol. The choroid plexuses and intraventricular ependymal cells and ventricle volumes were assessed and compared statistically.Results Degenerated epithelial cell density of 22 ± 5, 56 ± 11, 175 ± 37, and 356 ± 85/mm3 was found in the control, sham, low alcohol exposure, and high alcohol exposure groups, respectively. The Evans index was <34% in the control group, >36% in the sham group, >40% in the group exposed to low alcohol dose (low-dose alcohol group), and >50% in the group exposed to high dose of alcohol (high-dose alcohol group).Conclusions It was found that alcohol exposure caused choroid plexus and ependymal cell degeneration with ciliopathy and enlarged lateral ventricles or hydrocephalus. In the COVID-19 pandemic era, our findings are functionally important, because alcohol has often been used for hygiene and prevention of transmission of the Sars-Cov-2-virus.
Keywords: COVID-19; choroid plexus; ependymal cell; alcohol; hydrocephalus